Survey of women’s knowledge, Attitude and practice regarding prevention of common genital tract infection in Kerman health care centers in 2003 - J Farrokhzadian; Sh Zoherekermany; S Sabzevari; N Nakhei (JRI, 2004)
Introduction: Disease impedes normal and proper growth, and prevents health maintenance and health promotion. Therefore, necessary activities to prevent disease in the community should be considered as high priority issues in health and treatment programs. Genital tract infections are among diseases that threaten women’s health, thus preventing these infections is very important to control these diseases in the community. As prevention and control of STDs until 2010 is one of the major slogans of WHO and considering the increasing prevalence of these diseases in different societies, the need for education and consultation on sexual behavior and effective prevention of genital tract infectious diseases, especially STDs, must be considered as the core of any reproductive and sexual health care program. Since knowledge plays an important role in the people’s attitude and practice, obtaining knowledge and change in the attitude could eventually lead to the desired practice, too. This discriptive study carried out to asses knowledge, attitude and practice of women who referred to Kerman health care centers about prevention of common genital tract infections in 2003. Materials and Methods: The sample size included 305 women who were chosen by tow- stage cluster and by continuous nonprobability sampling method. The instrument for data collection was a researcher-made questionnaire with four parts including: demographic characteristics (14 questions), knowledge determina-tion (20 questions), attitude (12 sentences) and practice (16 sentences) about prevention of common genital tract infections. The questionnaire was used for data collection after through face to face interviews gaining nessesery validity and reliability. For data analysis, frequency table, t-test, spearman rank correlation cofficient, one way analysis of variance (ANOVA) and Tuckey test were used (α=0/05). Results: The results showed that women’s score for knowledge was 70% of total score, 80% for attitude and 80% for practice. There was a significant correlation between knowledge, attitude, and practice (P<0.01). Comparison of mean score of knowledge with demographic characteristics showed significant differences between knowledge and age groups (p< 0.05 ), level of education, level of spouse’s education and job (p<0.01). In comparision to mean score of attitude with demographic characteristics there was significant difference between attitude and level of education, level of spouse’s education, job (p<0.01), preventive method of pregnancy and previous information (p<0.05). Results also revealed that there was significant difference between mean score of practice with age groups (p<0.05), level of education, level of spouse’s education, job (p<0.01) and previous information (p<0.05). Conclusion: Results indicated that health services members have an important role in increasing knowledge and improving behaviours of community in prevention of common genital tract infection.
Keywords: Knowledge, Attitude, Practice, Genital tract infection, Prevention, Women